Organizational forms and technical efficiency of the dairy processing industry in Southern Brazil - Caetano Luiz Beber; Sebastian Lakner; Ioannis Skevas (Agricultural and Food Economics, 2021)
The objective of this article is to assess the determinants of the technical efficiency of dairy processing firms in Southern Brazil while accounting for their different organizational forms, namely cooperatives and investor-owned firms. The data from 243 milk processors in southern Brazil, including firm structure, management capacity, and organizational choice of dairies, were analyzed. A production frontier is specified to estimate technical efficiency and identify its potential driving sources. Bayesian techniques are used to estimate the model. An average efficiency of 77% indicates that the actual output is 23% below its potential, which implies that output could, on average, be increased by approximately 31.6%, under ceteris paribus conditions. Economies of scale were also detected. The analysis reveals that the management capacity within companies is the main determinant of efficiency. Idle capacities of processing plants are an important source of inefficiencies and cooperatives are more efficient than investor-owned firms, despite their transaction costs potentially being higher and the five vaguely defined property rights inherent to the traditional cooperatives which they must overcome. Knowledge about the cooperatives' objectives other than profit maximization would provide a more realistic comparison against investor-owned firms. This study assessed the determinants of the efficiency levels of dairy processing companies in an emerging economy using a unique own dataset with data collected at a plant level. Based on the results, manifold managerial and political implications have been derived that can benefit the dairy industry of developing and emerging economies.
Keywords: 330; Brazilian dairy sector; Dairy cooperatives; Dairy processing firms; Technical efficiency